Comparative Genomics of Thaumarchaeota From Deep-Sea Sponges Reveal Their Niche Adaptation - Wang, Peng; Li, Minchun; Dong, Liang; Zhang, Cheng; Xie, Wei (Frontiers in Microbiology, 2022)
Thaumarchaeota, ammonia-oxidizing archaea, account for a large portion of microbial symbionts in deep-sea sponges and are even dominant in some cases. In this study, we investigated three newly reported Thaumarchaeota of a sponge from the deep West Pacific Ocean. Thaumarchaeota were found to be the most dominant phylum in this sponge by both prokaryotic 16S rRNA amplicons and metagenomic sequencing. Other 57 published Thaumarchaeota genomes from sponges and other habitats were included for phylogenetic and genomic comparison. Similar to shallow sponge-associated Thaumarchaeota, those Thaumarchaeota in deep-sea sponges have extended genome sizes and lower coding density compared with their free-living lineages. Thaumarchaeota in deep-sea sponges were specifically found to be enriched in genes related to stress adapting, symbiotic adhesion and stability, host-microbe interaction and protein transportation. The defense mechanisms, such as the restriction-modification system, clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system, and toxin-antitoxin system were commonly found in both shallow and deep sponge-associated Thaumarchaeota. Our study demonstrates the significant effects of both depth and symbiosis on forming genomic characteristics of Thaumarchaeota, and provides novel insights into their niche adaptation in deep-sea sponges.